Does Co-worker Presenteeism Increase Innovative Behavior? Evidence From IT Professionals Under the 996 Work Regime in China - Yang, Tianan; Liu, Ran; Deng, Jianwei (Frontiers in Psychology, 2021)
Drawing on the event system and regulatory focus theories, this study constructed an impact mechanism model to investigate the relationship between the event strength of co-worker presenteeism and innovative behaviour among IT professionals under the 996 work regime. In addition to testing the direct effect, we examined the indirect effect of promotion focus and the moderating effect of event time in this relationship. Data were collected through an online survey administered to 376 IT professionals in China. The results showed a positive relationship between the criticality of co-worker presenteeism events and innovative behaviour. An indirect effect of promotion focus was also found in this relationship. The timing of co-worker presenteeism events moderated the relationship between the criticality of co-worker presenteeism events and promotion focus. Specifically, the effect was more significant when co-worker presenteeism events occurred during project delays.